EFEKTIVITAS PEMBELAJARAN KIMIA DENGAN PENDEKATAN SALINGTEMAS DITINJAU DARI MINAT DAN HASIL BELAJAR SISWA - -, Nuryanto; Binadja, Achmad (Jurnal Inovasi Pendidikan Kimia, 2010)
According to the most of students, chemistry is an abstract and diffi cult subject.The learning approach that can attract the students’ interest and correlate the science,environment, technology, and society aspects, and therefore enhance the students’ academicresult, should be applied. This research was conducted using quasi-experimental methodwith cluster random sampling technique. The developed instruments consist of the learningsets using salingtemas approach, test sets, observation and questionnaire sheets. The resultof this research shows that the chemistry learning on chemical bond topic using salingtemasapproach is effective to enhance the students’ academic result and come up the students’learning interest. The implementation of chemistry learning using salingtemas approach issuggested to be performed using more variative method in order to more improvement ofstudents’ interest and academic result.Key words: effectiveness, Salingtemas, Interest, academic result